Exploring Open Educational Resources for College Algebra - Chiorescu, Marcela (International Review of Research in Open and Distributed Learning, 2017)
It is estimated that the average student spends around 1200 USD on books and supplies every school year; thus, textbook affordability has become more and more of a challenge for students. Replacing traditionally expensive learning resources with open educational resources (OER) can have a great impact in the reduction of cost for post-secondary education and student learning. With these benefits as a backdrop, this article describes a case study in which one college instructor adopted OER for College Algebra, offered as a hybrid learning model. This paper discusses this experience with adopting such materials and their impact on student success.